PENERAPAN MODEL PEMBELAJARAN CONCEPTUAL UNDERSTANDING PROCEDURES (CUPs ) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VII.2 SMP NEGERI 3 SIKAKAP - Eka Mirawati; Anna Cesaria; Hamdunah Hamdunah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This research is motivated by students' low mathematical conceptual understanding. The purpose of this study was to determine whether students' mathematical conceptual understanding using the Conceptual Understanding Procedures (CUPs) model improves compared to before implementing the model in class VII.2 of SMP Negeri 3 Sikakap. This study used a pre-experimental study with a pretest-posttest group design. The population was grade VII students of SMP Negeri 3 Sikakap in the 2024/2025 academic year, consisting of two classes. The sampling technique used was purposive sampling, with class VII.2 selected as the sample class. The instruments used were a pre-test and post-test in the form of essays to measure students' mathematical conceptual understanding. Data analysis showed that the average score for the pre-test class was 73.5 and the average score for the post-test class was 82.92. The results of the hypothesis test obtained t_count = 12.34 and t_table = 2.160 with a level of ? = 0.05, so t_count t_table so it can be concluded that the ability to understand mathematical concepts of students with the application of the Conceptual Understanding Procedures (CUPs) Model is better than before applying the Conceptual Understanding Procedures (CUPs) Model.